Mongolia : Improved Space Heating Stoves for Ulaanbaatar - World Bank (Washington, DC, 2014)
Access to a reliable source of heat is vital to sustain life in Mongolia. Particularly so, for families living in the traditional tents, who today in Ulaanbaatar - the capital city - rely on burning mineral coal. However, the incomplete combustion of coal by inefficient metal stoves, releases polluting gases, affecting not only households' interior, but the air quality of the entire city. Additionally, air pollution is also caused by three central combined heating, and power stations coal-fueled boilers, and vehicle emissions. Over the 1999-2001 period, the Energy Sector Management Assistance Programme (ESMAP) assessed the situation in terms of household heating habits, and consumption levels, and identified the main local participants, towards improving stoves and their impact on air pollution. Appropriate schemes were designed for widespread uses, and a dissemination program was elaborated, including financial support from the Global Environment Facility (GEF) for its implementation. The report presents the findings, and lessons learned, highlighting the need to further explore other alternatives, such as the use of briquettes, installation of thermal bricks inside combustion chambers, and extending credit to consumers, increasing their purchasing power. It further stipulates fuel expenses can be cut by one-third, air pollution reduced, thus improving living conditions, public health, as well as public expenses, and the environment.